Unveiling tetrahydroquinolines as promising BVDV entry inhibitors: Targeting the envelope protein - Leal, Emilse Soledad (2024)
Bovine viral diarrhea virus (BVDV) is known to cause financial losses and decreased productivity in the cattle industry worldwide. Currently, there are no available antiviral treatments for effectively controlling BVDV infections in laboratories or farms. The BVDV envelope protein (E2) mediates receptor recognition on the cell surface and is required for fusion of virus and cell membranes after the endocytic uptake of the virus during the entry process. Therefore, E2 is an attractive target for the development of antiviral strategies. To identify BVDV antivirals targeting E2 function, we defined a binding site in silico located in domain IIIc at the interface between monomers in the disulfide linked dimer of E2. Employing a de novo design methodology to identify compounds with the potential to inhibit the E2 function, compound 9 emerged as a promising candidate with remarkable antiviral activity and minimal toxicity. In line with targeting of E2 function, compound 9 was found to block the virus entry into host cells. Furthermore, we demonstrated that compound 9 selectively binds to recombinant E2 in vitro. Molecular dynamics simulations (MD) allowed describing a possible interaction pattern between compound 9 and E2 and indicated that the S enantiomer of compound 9 may be responsible for the antiviral activity. Future research endeavors will focus on synthesizing enantiomerically pure compounds to further support these findings. These results highlight the usefulness of de novo design strategies to identify a novel class of BVDV inhibitors that block E2 function inhibiting virus entry into the host cell.